Hubungan antara Kepemimpinan Spiritual dan Kinerja Wirausaha Halal: Studi Empiris pada Komunitas Bisnis Syariah - Muhammad Danil (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the relationship between spiritual leadership and the performance of halal entrepreneurs in the Indonesian sharia business community. Spiritual leadership, which reflects the values ​​of monotheism, sincerity, trustworthiness, and moral responsibility, is believed to be a crucial element in shaping sustainable and sharia-compliant business behavior. This research method was quantitative, with a survey approach involving 100 business actors within the sharia business community. Data were analyzed using simple linear regression. The results indicate that spiritual leadership significantly influences the performance of halal entrepreneurs, both in terms of business sustainability, compliance with sharia principles, and customer satisfaction. These findings indicate that strengthening spiritual values ​​in leadership can be an important strategy in developing the sharia entrepreneurial ecosystem in the modern era.